A corrosion-resistant steel-plastic composite tape for cable coating and its preparation process
By combining fluorine-containing epoxy resin and corrosion inhibitor modified filler with steel strip, corrosion-resistant steel-plastic composite belt is prepared, which solves the problem of insufficient corrosion resistance of traditional cable coating materials and achieves cable coating materials with high mechanical strength and excellent corrosion resistance.
Patent Information
- Application Number
- CN202411350111.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Traditional cable coating materials have problems such as insufficient corrosion resistance and insufficient mechanical strength, which leads to the cable being easily corroded and damaged in harsh environments, affecting its performance and safety.
The steel-plastic composite belt is used as the cable coating material. By combining components such as fluorine-containing epoxy resin, corrosion-inhibiting modified filler and photoinitiator with the steel belt, a corrosion-resistant film liquid is formed, and a corrosion-resistant steel-plastic composite belt is prepared through ultraviolet curing and hot pressing composite processes.
It significantly improves the corrosion resistance and mechanical strength of the steel-plastic composite belt, extends the service life of the cable, and enhances its reliability and safety in harsh environments.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel-plastic composite tapes, in particular to a corrosion-resistant steel-plastic composite tape for cable coating and a preparation process thereof. Background Art
[0002] In modern industrial applications, the corrosion resistance and long-term reliability of cables are crucial. Cable coating materials need to have excellent corrosion resistance to ensure the service life of cables in harsh environments. However, traditional cable coating materials often have problems such as insufficient corrosion resistance and insufficient mechanical strength. These problems make cables susceptible to corrosion and damage in practical applications, thus affecting their performance and safety.
[0003] In order to solve these problems, steel-plastic composite tape has gradually attracted attention as a new type of cable covering material. The steel-plastic composite tape combines steel tape and plastic layer through composite technology, which can not only provide excellent mechanical strength, but also effectively prevent corrosion. In particular, the application of corrosion-resistant layer on the surface of steel tape is crucial to improving the corrosion resistance of the overall composite tape. The corrosion-resistant layer on the surface of steel tape is usually composed of special corrosion-resistant coating or metal coating, which can form a protective film on the surface of steel tape to prevent corrosive media from directly contacting the steel tape, thereby significantly improving the corrosion resistance and service life of the steel tape.
[0004] Therefore, developing a steel-plastic composite tape with excellent corrosion resistance and exploring its preparation process is an important way to improve the performance of cable coating materials. This can not only improve the durability and safety of the cable, but also meet the industry's high performance requirements for cable materials. Summary of the invention
[0005] The object of the present invention is to provide a corrosion-resistant steel-plastic composite tape for cable coating and a preparation process thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A preparation process for a corrosion-resistant steel-plastic composite tape for cable coating, comprising the following steps: S1: adding a fluorine-containing monomer, phenol, hydrochloric acid and Lewis acid into a reaction container, heating to 80-82°C for reaction for 4-4.5h, further heating to 200°C, washing the product with deionized water, pouring the product into an ethanol solution, filtering and crystallizing to obtain a dihydroxy fluorine-containing monomer; adding a dihydroxy fluorine-containing monomer, epichlorohydrin and a phase transfer catalyst into a reaction container, heating to 80-82°C for reaction for 60-65min, adding half of the sodium hydroxide alkali solution, controlling the reaction temperature to 75-85°C for reflux reaction for 2-2.5h, when the reaction temperature is cooled to 65-70°C, adding benzene and the remaining half of the sodium hydroxide alkali solution, reflux reaction for 160-180min, washing with deionized water, separating the liquids, collecting the aqueous phase, removing the benzene by reduced pressure distillation to obtain a fluorine-containing epoxy resin;
[0008] Further, in the dihydroxy fluorine-containing monomer, the molar ratio of fluorine-containing monomer to phenol is 1:2;
[0009] Furthermore, in the fluorinated epoxy resin, the molar ratio of dihydroxy fluorinated monomer to epichlorohydrin is 1:(10-12);
[0010] Furthermore, the amount of the phase transfer catalyst added is 1% of the total mass of the dihydroxy fluorinated monomer and epichlorohydrin;
[0011] Further, the concentration of the sodium hydroxide base is 28.6-32.2wt%;
[0012] Further, the phase transfer catalyst includes any one of tetraethylammonium chloride, tetramethylammonium chloride, tetramethylammonium bromide, tetrabutylammonium chloride, benzyltrimethylammonium chloride, and benzyltriethylammonium chloride;
[0013] Further, the phase transfer catalyst includes tetraethylammonium chloride;
[0014] S2: Add fluorinated epoxy resin to a reaction vessel, preheat to 70-72°C, add dibutyl phosphate for 1 hour, heat to 90-92°C and react for 3-3.5 hours to obtain fluorinated phosphorus diol; add toluene diisocyanate to a reaction vessel, preheat to 40-50°C, add hydroquinone, dibutyltin dilaurate, and hydroxyethyl acrylate, keep warm and react until the isocyanate group of the system no longer changes, add fluorinated forest diol, heat to 70-72°C and react until the isocyanate group of the system reaches the theoretical value, and obtain fluorinated phosphorus epoxy polyurethane acrylate;
[0015] Furthermore, in the fluorine-containing phosphorus diol, the molar ratio of epoxy group of the fluorine-containing epoxy resin to dibutyl phosphate is 1:1;
[0016] Furthermore, in the fluorine-containing phosphorus epoxy polyurethane acrylate, the molar ratio of fluorine-containing glycol: toluene diisocyanate: hydroxyethyl acrylate is 1:1:1;
[0017] Furthermore, the theoretical value of isocyanate groups is less than 0.5%;
[0018] S3: Add 3,4-dimethoxythiophene, 2,2-dibutyl-1,3-propanediol and p-toluenesulfonic acid to toluene, stir evenly, heat to reflux reaction for 1 day, wash with deionized water, remove toluene under vacuum, and purify the crude product on silica gel column chromatography with 3:2 hexane / dichloromethane as eluent to obtain product A; add product A to chloroform, pass argon, add N-bromosuccinimide, stir at room temperature for 4-5 hours, remove chloroform under vacuum, and purify the crude product on silica gel column chromatography with 8:2 hexane / dichloromethane as eluent to obtain product A. The product was purified by using alkane / dichloromethane as an eluent to obtain dibutyl dibromide (3,4-propylenedioxythiophene); dibutyl substituted dibromide (3,4-propylenedioxythiophene) and methylmagnesium chloride were added to tetrahydrofuran, nitrogen was introduced, the mixture was heated to 45-46°C and reacted for 50-60 minutes, 1,2-bis(diphenylphosphine ethane) nickel chloride was added, the mixture was heated to 49.85-50°C and reacted for 1-1.5 hours, the product was poured into hexane, filtered, the precipitate was purified by methanol precipitation, and vacuum dried to obtain a corrosion inhibitor;
[0019] Furthermore, in the product A, the molar ratio of 3,4-dimethoxythiophene:2,2-dibutyl-1,3-propanediol is 1:1;
[0020] Furthermore, in the dibutyl dibromide (3,4-propylenedioxythiophene), the molar ratio of product A: N-bromosuccinimide is 3.7:11.1;
[0021] Furthermore, in the corrosion inhibitor, the molar ratio of dibutyl substituted dibromo(3,4-propylenedioxythiophene):methylmagnesium chloride:1,2-bis(diphenylphosphineethane)nickel chloride is 0.94:0.9:0.2;
[0022] S4: Add hexadecylamine and 0.1M potassium chloride to methanol, add titanium isopropoxide, stir evenly, let stand for 24 hours, wash with ethanol, add the product to 50% v / v ethanol solution, heat to 160-161°C for reaction for 15-16 minutes, wash with deionized water and ethanol alternately, and vacuum dry at 60°C for 12 hours to obtain mesoporous titanium dioxide; ultrasonically disperse the mesoporous titanium dioxide and corrosion inhibitor in ethanol, stir under negative pressure for 6-7 hours, centrifuge, and dry to obtain loaded mesoporous silica; disperse the loaded mesoporous silica in chloroform, add 3-(methacryloyloxy)propyltrimethoxysilane, heat to 70-75°C for reaction for 12 hours, centrifuge, and wash to obtain a corrosion inhibitor modified filler;
[0023] Furthermore, in the mesoporous titanium dioxide, the mass ratio of titanium isopropoxide to hexadecylamine is (4.5-5.5): (1.53-1.55);
[0024] Furthermore, in the loaded mesoporous silica, the mass ratio of mesoporous titanium dioxide to corrosion inhibitor is (0.4-0.5):3;
[0025] Furthermore, in the corrosion inhibitor modified filler, the mass ratio of loaded mesoporous silica to 3-(methacryloyloxy)propyltrimethoxysilane is 1:1;
[0026] S5: Evenly mix fluorine-phosphorus epoxy polyurethane acrylate, corrosion inhibitor modified filler, photoinitiator and active monomer to obtain corrosion-resistant film liquid; apply it on both surfaces of the steel strip, place it under ultraviolet light for curing for 3-5 minutes to obtain a base steel strip; hot-press the base steel strip and polyethylene plastic film, cool it, and roll it up to obtain a corrosion-resistant steel-plastic composite strip.
[0027] Furthermore, the proportion of each component in the corrosion-resistant membrane liquid includes, by weight: 60-80 parts of fluorine-phosphorus epoxy polyurethane acrylate, 3-5 parts of corrosion inhibitor modified filler, 4-6 parts of photoinitiator, and 20-40 parts of active monomer;
[0028] Furthermore, the active monomers include trimethylolpropane triacrylate and polyethylene glycol methacrylate phosphate in a mass ratio of (1-2):1;
[0029] Further, the coating thickness is 50-100 μm;
[0030] Further, the photoinitiator is photoinitiator TPO;
[0031] Furthermore, the thickness of the polyethylene film is 0.03-0.05 mm;
[0032] Furthermore, the steel strip is a SPCC chrome-plated steel strip with a thickness of 0.1-0.12 mm.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention selects commercially available fluorine-containing compounds as raw materials to react with phenol to obtain fluorine-containing diol monomers, which are etherified with epichlorohydrin under the catalytic action of a catalyst to prepare a fluorine-containing epoxy resin, which is different from traditional commercially available traditional epoxy resins such as bisphenol A diglycidyl ether, and externally added fluorine monomers. The introduction of fluorine element into epoxy resin, on the one hand, provides excellent cleaning performance and corrosion resistance, and on the other hand, does not affect the compatibility and dispersibility of the epoxy resin matrix, providing an excellent corrosion-resistant matrix epoxy resin for the preparation of corrosion-resistant membrane liquid. The radiation-cured coating based on the prepared prepolymer has the advantages of epoxy acrylate and polyurethane acrylate coating.
[0035] 2. In this study, a new type of solution-processable dibutyl-substituted poly (3,4-propylenedioxythiophene) was synthesized by Grignard metathesis polymerization and added to the resin matrix as a corrosion inhibitor to enhance the corrosion resistance of the membrane solution. The purpose is to solve the problem that traditional poly (3,4-ethylenedioxythiophene) corrosion inhibitors are difficult to be uniformly incorporated into polymer resins. The electroactive poly (3,4-propylenedioxythiophene) catalyzes ferrous ions to form a passivation layer on the steel surface, thereby resisting the corrosion of oxygen, water vapor and corrosive ions on the metal.
[0036] 3. In order to further increase the proportion of corrosion inhibitor in the membrane liquid, the present invention uses mesoporous titanium dioxide for loading to achieve an increase in the proportion of corrosion inhibitor in the membrane liquid per unit amount. Further grafting is performed on the surface of the loaded mesoporous titanium dioxide so that the surface carries unsaturated double bonds to participate in the ultraviolet light polycondensation curing of the membrane liquid, further improving its dispersibility and compatibility in the resin matrix, improving the density of the film formed by the membrane liquid on the surface of the steel strip, and further improving the corrosion resistance of the steel-plastic composite strip. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In the following examples, the fluorinated monomer CAS: 80180-03-6 was purchased from Zhuhai Aobokai Biopharmaceutical Technology Co., Ltd.; the remaining raw materials were commercially available.
[0039] In the following embodiments, the preparation method of fluorine-containing epoxy resin comprises the following steps: adding 1 mol fluorine-containing monomer, 2 mol phenol, 0.01 mol hydrochloric acid and 0.02 mol Lewis acid to a reaction vessel, heating to 80°C for reaction for 4 h, further heating to 200°C, washing the product with deionized water, pouring the product into an ethanol solution, filtering and crystallizing to obtain a dihydroxy fluorine-containing monomer; adding 1 mol dihydroxy fluorine-containing monomer, 10 mol epichlorohydrin and 1 wt% tetraethylammonium chloride to a reaction vessel, heating to 80°C for reaction for 60 min, adding half of 28.6 wt% sodium hydroxide lye, controlling the reaction temperature to 75°C for reflux reaction for 2 h, when the reaction temperature is cooled to 65°C, adding benzene and the remaining half of 28.6 wt% sodium hydroxide lye, reflux reaction for 160 min, washing with deionized water, separating the liquids, collecting the aqueous phase, and removing benzene by reduced pressure distillation to obtain a fluorine-containing epoxy resin.
[0040] In the following embodiments, the preparation method of the corrosion inhibitor comprises the following steps: adding 1 mmol 3,4-dimethoxythiophene, 1 mmol 2,2-dibutyl-1,3-propanediol, and 5 g p-toluenesulfonic acid to toluene, stirring evenly, heating to reflux reaction for 1 day, washing with deionized water, removing toluene under vacuum, and purifying the crude product on silica gel column chromatography with 3:2 hexane / dichloromethane as eluent to obtain product A; adding 3.7 mmol product A to chloroform, passing argon gas, adding 11.1 mmol N-bromosuccinimide, stirring at room temperature for 4 hours, and vacuum drying. After removing chloroform, the crude product was purified on a silica gel column using 8:2 hexane / dichloromethane as an eluent to obtain dibutyl dibromide (3,4-propylenedioxythiophene); 0.94mmol of dibutyl substituted dibromide (3,4-propylenedioxythiophene) and 0.9mmol of methylmagnesium chloride were added to tetrahydrofuran, nitrogen was introduced, and the mixture was heated to 45°C for 50min. 0.2mmol of 1,2-bis(diphenylphosphineethane)nickel chloride was added and the mixture was heated to 49.85°C for 1h. The product was poured into hexane and filtered. The precipitate was purified by methanol precipitation and dried in vacuo to obtain a corrosion inhibitor.
[0041] Embodiment 1: A process for preparing a corrosion-resistant steel-plastic composite tape for cable coating: S1: Add 1 mol of fluorine-containing epoxy resin to a reaction container, preheat to 70°C, add 1 mol of dibutyl phosphate for 1 hour, heat to 90°C and react for 3 hours to obtain fluorine-containing phosphorus diol; add 1 mol of toluene diisocyanate to a reaction container, preheat to 40°C, add 0.02 mol of hydroquinone, 0.01 mol of dibutyltin dilaurate, and 1 mol of hydroxyethyl acrylate, keep warm and react until the isocyanate group of the system no longer changes, add 1 mol of fluorine-containing forest diol, heat to 70°C and react until the isocyanate group of the system reaches the theoretical value, and obtain fluorine-containing phosphorus epoxy polyurethane acrylate;
[0042] S2: Add 4.5g hexadecylamine and 0.1M potassium chloride to methanol, add 1.53g titanium isopropoxide, stir evenly, let stand for 24h, wash with ethanol, add the product to 50% v / v ethanol solution, heat to 160℃ for reaction for 15min, wash with deionized water and ethanol alternately, and vacuum dry at 60℃ for 12h to obtain mesoporous titanium dioxide; ultrasonically disperse 0.4g mesoporous titanium dioxide and 3g corrosion inhibitor in ethanol, stir under negative pressure for 6h, centrifuge, and dry to obtain loaded mesoporous silica; disperse 1g loaded mesoporous silica in chloroform, add 1g 3-(methacryloyloxy)propyltrimethoxysilane, heat to 70℃ for reaction for 12h, centrifuge, and wash to obtain corrosion inhibitor modified filler;
[0043] S3: Evenly mix 80 parts of fluorine-phosphorus epoxy polyurethane acrylate, 3 parts of corrosion inhibitor modified filler, 4 parts of photoinitiator, 10 parts of trimethylolpropane acrylate and 10 parts of polyethylene glycol methacrylate phosphate to obtain a corrosion-resistant film liquid; apply it on both surfaces of the steel strip, place it under ultraviolet light for curing for 3 minutes, and obtain a base steel strip; hot-press the base steel strip and the polyethylene plastic film, cool it, and roll it up to obtain a corrosion-resistant steel-plastic composite strip.
[0044] Example 2: A preparation process for a corrosion-resistant steel-plastic composite tape for cable coating: S3: Mix 70 parts of fluorine-phosphorus epoxy polyurethane acrylate, 3 parts of corrosion inhibitor modified filler, 4 parts of photoinitiator, 15 parts of trimethylolpropane acrylate and 15 parts of polyethylene glycol methacrylate phosphate to obtain a corrosion-resistant film liquid; apply it on both surfaces of a steel strip, place it under ultraviolet light for curing for 3 minutes, and obtain a base steel strip; hot-press the base steel strip and a polyethylene plastic film, cool it, and roll it up to obtain a corrosion-resistant steel-plastic composite tape.
[0045] The remaining steps are the same as those in Example 1.
[0046] Example 3: A preparation process for a corrosion-resistant steel-plastic composite tape for cable coating: S3: Mix 60 parts of fluorine-phosphorus epoxy polyurethane acrylate, 3 parts of corrosion inhibitor modified filler, 4 parts of photoinitiator, 20 parts of trimethylolpropane acrylate and 20 parts of polyethylene glycol methacrylate phosphate to obtain a corrosion-resistant film liquid; apply it on both surfaces of a steel strip, place it under ultraviolet light for curing for 3 minutes, and obtain a base steel strip; hot-press the base steel strip and a polyethylene plastic film, cool it, and wind it up to obtain a corrosion-resistant steel-plastic composite tape.
[0047] The remaining steps are the same as those in Example 1.
[0048] Example 4: A preparation process for a corrosion-resistant steel-plastic composite tape for cable coating: S3: Evenly mix 70 parts of fluorine-phosphorus epoxy polyurethane acrylate, 5 parts of corrosion inhibitor modified filler, 4 parts of photoinitiator, 15 parts of trimethylolpropane acrylate and 15 parts of polyethylene glycol methacrylate phosphate to obtain a corrosion-resistant film liquid; apply it on both surfaces of a steel strip, and cure it under ultraviolet light for 3 minutes to obtain a base steel strip; hot-press the base steel strip and a polyethylene plastic film, cool it, and wind it up to obtain a corrosion-resistant steel-plastic composite tape.
[0049] The remaining steps are the same as those in Example 1.
[0050] Comparative Example 1: A preparation process for a corrosion-resistant steel-plastic composite tape for cable coating: S1: Add 1 mol of bisphenol A diglycidyl ether to a reaction container, preheat to 70°C, add 1 mol of dibutyl phosphate for 1h, heat to 90°C for reaction for 3h, and obtain fluorine-containing phosphorus diol; add 1 mol of toluene diisocyanate to a reaction container, preheat to 40°C, add 0.02 mol of hydroquinone, 0.01 mol of dibutyltin dilaurate, and 1 mol of hydroxyethyl acrylate, and keep warm to react until the isocyanate group of the system no longer changes, add 1 mol of fluorine-containing forest diol, heat to 70°C for reaction until the isocyanate group of the system reaches the theoretical value, and obtain fluorine-containing phosphorus epoxy polyurethane acrylate;
[0051] The remaining steps are the same as those in Example 1.
[0052] Comparative Example 2: A process for preparing a corrosion-resistant steel-plastic composite tape for cable coating: S3: 80 parts of fluorine-phosphorus epoxy polyurethane acrylate, 3 parts of corrosion inhibitor modified filler, 4 parts of photoinitiator, 10 parts of trimethylolpropane acrylate and 10 parts of polyethylene glycol methacrylate phosphate are mixed evenly to obtain a corrosion-resistant film liquid; the film liquid is coated on both surfaces of a steel strip, and cured under ultraviolet light for 3 minutes to obtain a base steel strip; the base steel strip is hot-pressed and laminated with a polyethylene plastic film, cooled, and rolled to obtain a corrosion-resistant steel-plastic composite tape;
[0053] The remaining steps are the same as those in Example 1.
[0054] Comparative Example 3: A process for preparing a corrosion-resistant steel-plastic composite tape for cable coating: S1: Add 1 mol of fluorine-containing epoxy resin to a reaction container, preheat to 70°C, add 1 mol of dibutyl phosphate for 1h, heat to 90°C and react for 3h to obtain fluorine-containing phosphorus diol; add 1 mol of toluene diisocyanate to a reaction container, preheat to 40°C, add 0.02 mol of hydroquinone, 0.01 mol of dibutyltin dilaurate and 1 mol of hydroxyethyl acrylate, keep warm and react until the isocyanate group of the system no longer changes, add 1 mol of fluorine-containing diol, heat to 70°C and react until the isocyanate group of the system reaches the theoretical value, and obtain fluorine-containing phosphorus epoxy polyurethane acrylate;
[0055] S2: 80 parts of fluorine-phosphorus epoxy polyurethane acrylate, 3 parts of corrosion inhibitor, 4 parts of photoinitiator, 10 parts of trimethylolpropane acrylate and 10 parts of polyethylene glycol methacrylate phosphate are mixed evenly to obtain a corrosion-resistant film liquid; the film liquid is coated on both surfaces of a steel strip, and cured under ultraviolet light for 3 minutes to obtain a base steel strip; the base steel strip is hot-pressed and laminated with a polyethylene plastic film, cooled, and rolled to obtain a corrosion-resistant steel-plastic composite strip.
[0056] Comparative Example 4: A process for preparing a corrosion-resistant steel-plastic composite tape for cable coating: S1: Add 1 mol of fluorine-containing epoxy resin to a reaction container, preheat to 70°C, add 1 mol of dibutyl phosphate for 1 hour, heat to 90°C and react for 3 hours to obtain fluorine-containing phosphorus diol; add 1 mol of toluene diisocyanate to a reaction container, preheat to 40°C, add 0.02 mol of hydroquinone, 0.01 mol of dibutyltin dilaurate, and 1 mol of hydroxyethyl acrylate, keep warm and react until the isocyanate group of the system no longer changes, add 1 mol of fluorine-containing diol, heat to 70°C and react until the isocyanate group of the system reaches the theoretical value, and obtain fluorine-containing phosphorus epoxy polyurethane acrylate;
[0057] S2: Add 4.5g hexadecylamine and 0.1M potassium chloride to methanol, add 1.53g titanium isopropoxide, stir evenly, let stand for 24h, wash with ethanol, add the product to 50% v / v ethanol solution, heat to 160°C for 15min, wash with deionized water and ethanol alternately, and vacuum dry at 60°C for 12h to obtain mesoporous titanium dioxide; ultrasonically disperse 0.4g mesoporous titanium dioxide and 3g corrosion inhibitor in ethanol, stir under negative pressure for 6h, centrifuge, and dry to obtain loaded mesoporous silica;
[0058] S3: Evenly mix 80 parts of fluorine-phosphorus epoxy polyurethane acrylate, 3 parts of loaded mesoporous silica, 4 parts of photoinitiator, 10 parts of trimethylolpropane acrylate and 10 parts of polyethylene glycol methacrylate phosphate to obtain a corrosion-resistant film liquid; apply it on both surfaces of a steel strip, place it under ultraviolet light for curing for 3 minutes, and obtain a base steel strip; hot-press the base steel strip and a polyethylene plastic film, cool it, and roll it up to obtain a corrosion-resistant steel-plastic composite strip.
[0059] Comparative Example 5: S3: 80 parts of fluorine-phosphorus epoxy polyurethane acrylate, 10 parts of corrosion inhibitor modified filler, 4 parts of photoinitiator, 10 parts of trimethylolpropane acrylate and 10 parts of polyethylene glycol methacrylate phosphate are mixed evenly to obtain a corrosion-resistant film liquid; the film liquid is applied on both surfaces of a steel strip, and cured under ultraviolet light for 3 minutes to obtain a substrate steel strip; the substrate steel strip is hot-pressed and laminated with a polyethylene plastic film, cooled, and rolled to obtain a corrosion-resistant steel-plastic composite strip.
[0060] The remaining steps are the same as those in Example 1.
[0061] Experiment: The following test object is the base steel strip.
[0062] Adhesion test: Tested using the cross-cut adhesion method in accordance with GB / T 9286-1998;
[0063] Corrosion resistance experiment: The electrochemical performance of the coating was tested using a CHI660D electrochemical workstation from Swiss Metrohm China Ltd. A three-electrode working system was used. The working electrode, reference electrode, and counter electrode were steel specimens coated with epoxy resin, saturated calomel, and platinum sheets, respectively. During the test, the exposed area of the working electrode in the reaction cell was 1 cm 2 , the open circuit voltage is used as the starting voltage during EIS measurement, and the frequency is 0.01~10 5 Hz, the interference signal is 10mV, and the test medium is 3% by mass NaCl solution; the experimental data R is the charge transfer resistance of the coating; C is the water absorption performance of the coating. The higher R and the lower C are, the better the corrosion resistance of the coating is.
[0064] The experimental data are shown in Table 1 below.
[0065] Table 1 Corrosion-resistant steel-plastic composite belt performance test data
[0066] Adhesion / Grade <![CDATA[R / Ω·cm 2 ]]> <![CDATA[C / F·cm -2 ]]> Example 1 0 <![CDATA[3.4×10 6 ]]> <![CDATA[2.5×10 -10 ]]> Example 2 0 <![CDATA[6.4×10 6 ]]> <![CDATA[8.4×10 -11 ]]> Example 3 0 <![CDATA[5.2×10 6 ]]> <![CDATA[9.2×10 -11 ]]> Example 4 0 <![CDATA[1.2×10 7 ]]> <![CDATA[7.6×10 -11 ]]> Comparative Example 1 0 <![CDATA[1.2×10 6 ]]> <![CDATA[5.8×10 -10 ]]> Comparative Example 2 1 <![CDATA[1.6×10 6 ]]> <![CDATA[6.6×10 -10 ]]> Comparative Example 3 1 <![CDATA[9.5×10 5 ]]> <![CDATA[8.1×10 -10 ]]> Comparative Example 4 0 <![CDATA[2.8×10 6 ]]> <![CDATA[3.1×10 -10 ]]> Comparative Example 5 0 <![CDATA[2.4×10 6 ]]> <![CDATA[3.7×10 -10 ]]>
[0067] Conclusion: The corrosion-resistant steel-plastic composite belt prepared by the present invention has excellent corrosion resistance.
[0068] In Comparative Example 1, ordinary commercially available bisphenol A diglycidyl ether was used to replace the fluorine-containing epoxy resin, resulting in reduced hydrophobicity and corrosion resistance of the coating.
[0069] In Comparative Example 2, trimethylolpropane acrylate was selected as the only active monomer, and polyethylene glycol methacrylate phosphate active monomer was lacking, resulting in reduced adhesion to the metal surface of the steel strip and reduced corrosion resistance.
[0070] In Comparative Example 3, mesoporous titanium dioxide was not used to load the corrosion inhibitor, resulting in too much corrosion inhibitor without the help of mesoporous titanium dioxide at the same amount, causing the coating to deteriorate and the corrosion resistance to decrease.
[0071] In Comparative Example 4, the surface of the supported mesoporous titanium dioxide was not further modified, resulting in reduced dispersion performance in the membrane liquid and reduced corrosion resistance.
[0072] In Comparative Example 5, too much corrosion inhibitor filler was added, resulting in reduced dispersion performance of the slow-release filler in the membrane liquid, resulting in reduced corrosion resistance of the steel-plastic composite belt.
[0073] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A process for preparing a corrosion-resistant steel-plastic composite tape for cable coating, characterized in that: The following steps are involved: The fluorine-phosphorus epoxy polyurethane acrylate, the corrosion inhibitor modified filler, the photoinitiator and the active monomer are uniformly mixed to obtain a corrosion-resistant film liquid; Apply it on both surfaces of the steel strip, place it under ultraviolet light for curing for 3-5 minutes, and obtain a base steel strip; hot-press the base steel strip and the polyethylene plastic film, cool it, and roll it up to obtain a corrosion-resistant steel-plastic composite strip; The components in the corrosion-resistant membrane liquid include, by mass, 60-80 parts of fluorine-phosphorus epoxy polyurethane acrylate, 3-5 parts of corrosion inhibitor modified filler, 4-6 parts of photoinitiator, and 20-40 parts of active monomer; the active monomer includes trimethylolpropane triacrylate and polyethylene glycol methacrylate phosphate in a mass ratio of (1-2):1; The preparation method of the corrosion inhibitor modified filler comprises the following steps: adding hexadecylamine and 0.1M potassium chloride to methanol, adding titanium isopropoxide, stirring evenly, standing for 24 hours, washing with ethanol, adding the product to a 50% v / v ethanol solution, heating to 160-161° C. for reaction for 15-16 minutes, washing with deionized water and ethanol alternately, and vacuum drying at 60° C. for 12 hours to obtain mesoporous titanium dioxide; ultrasonically dispersing the mesoporous titanium dioxide and the corrosion inhibitor in ethanol, stirring under negative pressure for 6-7 hours, centrifuging, and drying to obtain loaded mesoporous titanium dioxide; dispersing the loaded mesoporous titanium dioxide in chloroform, adding 3-(methacryloyloxy)propyltrimethoxysilane, heating to 70-75° C. for reaction for 12 hours, centrifuging, and washing to obtain the corrosion inhibitor modified filler; The preparation method of the corrosion inhibitor comprises the following steps: adding 3,4-dimethoxythiophene, 2,2-dibutyl-1,3-propylene glycol and p-toluenesulfonic acid to toluene, stirring evenly, heating to reflux reaction for 1 day, washing with deionized water, removing toluene under vacuum, purifying to obtain product A; adding product A to chloroform, introducing argon, adding N-bromosuccinimide, stirring at room temperature for 4-5 hours, removing chloroform under vacuum, purifying to obtain dibutyldibromo-(3,4-propylenedioxythiophene); adding dibutyldibromo-(3,4-propylenedioxythiophene) and methylmagnesium chloride to tetrahydrofuran, introducing nitrogen, heating to 45-46°C for reaction for 50-60 minutes, adding 1,2-bis(diphenylphosphineethane)nickel chloride, heating to 49.85-50°C for reaction for 1-1.5 hours, pouring the product into hexane, filtering, purifying, and vacuum drying to obtain the corrosion inhibitor; The preparation method of fluorine-containing phosphorus epoxy polyurethane acrylate comprises the following steps: adding fluorine-containing epoxy resin into a reaction container, preheating to 70-72°C, adding dibutyl phosphate for 1h, heating to 90-92°C for reaction for 3-3.5h, and obtaining fluorine-containing phosphorus diol; adding toluene diisocyanate into a reaction container, preheating to 40-50°C, adding hydroquinone, dibutyltin dilaurate, and hydroxyethyl acrylate, keeping the temperature to react until the isocyanate group of the system no longer changes, adding fluorine-containing phosphorus diol, heating to 70-72°C for reaction until the isocyanate group of the system reaches a theoretical value, and obtaining fluorine-containing phosphorus epoxy polyurethane acrylate; The preparation method of the fluorine-containing epoxy resin comprises the following steps: adding a fluorine-containing monomer, phenol, hydrochloric acid and Lewis acid into a reaction container, heating to 80-82°C for reaction for 4-4.5h, heating to 200°C, washing the product, and crystallizing to obtain a dihydroxy fluorine-containing monomer; adding a dihydroxy fluorine-containing monomer, epichlorohydrin and a phase transfer catalyst into a reaction container, heating to 80-82°C for reaction for 60-65min, adding half of the amount of sodium hydroxide alkali solution, controlling the reaction temperature to 75-85°C for reflux reaction 2-2.5h, when the reaction temperature is cooled to 65-70°C, benzene and the remaining half of the sodium hydroxide alkali solution are added, reflux reaction is carried out for 160-180min, washing, separation, collecting the aqueous phase, and removing benzene by reduced pressure distillation to obtain a fluorine-containing epoxy resin; in the dihydroxy fluorine-containing monomer, the molar ratio of the fluorine-containing monomer: phenol is 1:2; in the fluorine-containing epoxy resin, the molar ratio of the dihydroxy fluorine-containing monomer: epichlorohydrin is 1:(10-12); the fluorine-containing monomer CAS: 80180-03-6.
2. The process for preparing the corrosion-resistant steel-plastic composite tape for cable coating according to claim 1, characterized in that: In the mesoporous titanium dioxide, the mass ratio of titanium isopropoxide:hexadecylamine is (4.5-5.5):(1.53-1.55); in the loaded mesoporous titanium dioxide, the mass ratio of mesoporous titanium dioxide:corrosion inhibitor is (0.4-0.5):3; in the corrosion inhibitor modified filler, the mass ratio of loaded mesoporous titanium dioxide:3-(methacryloyloxy)propyltrimethoxysilane is 1:
1.
3. The process for preparing the corrosion-resistant steel-plastic composite tape for cable coating according to claim 1, characterized in that: In the product A, the molar ratio of 3,4-dimethoxythiophene:2,2-dibutyl-1,3-propylene glycol is 1:1; in the dibutyl dibromo-(3,4-propylenedioxythiophene), the molar ratio of product A:N-bromosuccinimide is 3.7:11.1; in the corrosion inhibitor, the molar ratio of dibutyl dibromo-(3,4-propylenedioxythiophene):methylmagnesium chloride:1,2-bis(diphenylphosphineethane)nickel chloride is 0.94:0.9:0.
2.
4. The process for preparing the corrosion-resistant steel-plastic composite tape for cable coating according to claim 1, characterized in that: In the fluorine-containing phosphorus diol, the molar ratio of the epoxy group of the fluorine-containing epoxy resin to dibutyl phosphate is 1:1; in the fluorine-containing phosphorus epoxy polyurethane acrylate, the molar ratio of the fluorine-containing phosphorus diol to toluene diisocyanate to hydroxyethyl acrylate is 1:1:
1.
5. A steel-plastic composite tape prepared according to the preparation process of a corrosion-resistant steel-plastic composite tape for cable coating according to any one of claims 1 to 4.
Citation Information
Patent Citations
Novel catalyst for preparation of 3,4-propylenedioxythiophene and derivatives thereof
CN109382139A
Preparation method of vinyl anticorrosive resin coating
CN117925057A